Doing business in world markets : A comparative study - Ghazanfar, Anmol; Bolotov, Ilya; Cook, Gina, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The main aim of this bachelor thesis is to make the reader aware of the history, culture, and economy of the three countries: Russia, China, and Saudi Arabia. The thesis is divided into three parts, dedicated to the topics mentioned above. There is a conclusion presented at the end of each chapter that explains and compares the three countries. Before entering a foreign market, one must learn and become aware of these three main areas, as it (the knowledge) can be used as a helpful and informative aid when doing business in these countries that have a very high potential, interesting history, complex culture, and economy.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses